1978
DOI: 10.1017/s0305000900007406
|View full text |Cite
|
Sign up to set email alerts
|

Language development as related to stage 6 object permanence development

Abstract: A longitudinal study of three children examined the relation between object permanence and language development. Unlike other studies, an independent measure of object permanence development was provided. While there was not a one-to-one correspondence between object permanence and language, there were relations at certain points in development. There was a rough relationship between the onset of stage 6 of object permanence and the onset of single-word utterances. Total vocabulary showed a large increase arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
2
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 10 publications
2
79
2
1
Order By: Relevance
“…Thus, the theory outlined by Barrett (1995), that before about 18 months children are limited to context-bound words, social-pragmatic words, and affect expressions, is not supported by these data (see also Dore, 1985;Kamhi, 1986;McShane 1980; 1983). Relatedly, many theorists have considered the rapid progress in word production often seen at the end of the child's 2nd year and concluded that it is caused by the attainment of an insight about language (e.g., Corrigan, 1978;Dore, 1978;Golinkoff, Mervis, & Hirsh-Pasek, 1994;Gopnik & Meltzoff, 1987;Kamhi, 1986;McShane, 1979;Woodward & Markman, 1998). The results reported here are not consistent with this approach, nor with much of the traditional literature in cognitive development (Piaget, 1954;Vygotsky, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the theory outlined by Barrett (1995), that before about 18 months children are limited to context-bound words, social-pragmatic words, and affect expressions, is not supported by these data (see also Dore, 1985;Kamhi, 1986;McShane 1980; 1983). Relatedly, many theorists have considered the rapid progress in word production often seen at the end of the child's 2nd year and concluded that it is caused by the attainment of an insight about language (e.g., Corrigan, 1978;Dore, 1978;Golinkoff, Mervis, & Hirsh-Pasek, 1994;Gopnik & Meltzoff, 1987;Kamhi, 1986;McShane, 1979;Woodward & Markman, 1998). The results reported here are not consistent with this approach, nor with much of the traditional literature in cognitive development (Piaget, 1954;Vygotsky, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…Various theoretical accounts have been offered to explain the rapid linguistic development observed during the second year, such as the occurrence of a naming insight (McShane, 1979), changes in categorization abilities (Gopnik & Meltzoff, 1987), object permanence skills (Corrigan, 1978), and the emergence of speech segmentation abilities (Plunkett, 1993). Other approaches have argued that qualitative shifts in processing are not needed to explain linguistic development in the second year.…”
Section: Introductionmentioning
confidence: 99%
“…As illustrations, we tested our system on physical data of children's height from the Berkeley growth study (Tuddenham & Snyder, 1954), on simulated data of children's vocabulary size (McMurray, 2007;Mitchell & McMurray, 2008), and on experimental data of children's vocabulary size (Corrigan, 1978). We chose the first two problems because both of them have uncontroversial growth spurts that we expected AMD to find, a well-documented spurt during adolescence for physical growth (Tanner, 1978) and a large central spurt for simulated vocabulary data.…”
Section: Preprocessing Using Fdamentioning
confidence: 99%
“…Finally, we investigated vocabulary growth in real data from Corrigan (1978). These data were collected from 4,000 500 1,000 1,500 2,000 2,500 3,000 3,500 4,000 sample ID 500 1,000 1,500 2,000 2,500 3,000 3,500 4,000 sample ID 500 1,000 1,500 2,000 2,500 3,000 3,500 4,000 sample ID 500 1,000 1,500 2,000 2,500 3,000 3,500 4 cept of discontinuities rather than spurts.…”
Section: Real Vocabulary Growthmentioning
confidence: 99%